Pengembangan Usaha Layanan Sewa Boat Organisasi Panglima Laot Menuju BUMDes Mandiri di Kota Banda Aceh - Rahmattullah Rahmattullah (Duconomics Sci-meet (Education & Economics Science Meet), 2021)
The development of governance for boat rental services by the Panglima Laot organization in Banda Aceh City is needed as a manifestation of the achievement of the aspirations of the youth of Meuraxa District to have a BUMDes in an independent village administration administrative bureaucracy. For the change from this creative effort to BUMDes, it is necessary to reform the governance of business units that are currently being carried out in the establishment document. Currently, a boat rental business is running for fishing activities, both by local residents and by other residents who rent boat equipment in Meuraxa District. Besides, it is also used by tenants to do sea fishing as a hobby. This study aims to develop a boat rental service management system for the Panglima Laot organization through administrative reform of business unit management towards an independent BUMDes. This research is qualitative. In the development of this business, after reviewing the potential of both human and natural resources, it is found that this business service has the potential to increase income and prevent unemployment of the local community which results in reducing poverty rates in the assumption that all human and natural resources can work together. realize independent BUMDes. So that this creative business deserves to be developed to become a growing business for the future under the guidance of a village legal entity in the form of an Independent BUMDes.